Pengukuran Volume Overburden Menggunakan UAV di Pit 3HWE PT Indominco Mandiri: Measuring Overburden Volume Using UAV at Pit 3HWE PT Indominco Mandiri - Sendana, Aprianto Aris; Magdalena, Henny; Devy, Shalaho Dina; Trides, Tommy; Respati, Lucia Litha (MINERAL, 2025)
This study aims to measure the overburden volume at Pit 3HWE, PT. Indominco Mandiri using Unmanned Aerial Vehicle (UAV) technology. The use of UAV for volume measurement offers a more efficient and accurate alternative compared to conventional methods. In this research, aerial images were captured using a UAV and processed with photogrammetry software to generate a digital surface model (DSM) and 3D maps. The overburden volume calculations were analyzed and compared with manual measurement data as a reference. The results indicate that UAV usage provides accurate results with higher time efficiency, making it a viable method for mining operations. Factors affecting the measurement results, such as weather conditions and image resolution, were also analyzed in this study.